Science Literacy Profile of High School Students: Implications of PBL Didactic Design on the Topic of Microplastics - Salsabila, Syifa Ayugea (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study aims to analyze the science literacy profile of high school students following the implementation of a didactic problem-based learning (PBL) design on the topic of microplastics. This study adopted a Didactical Design Research (DDR) methodology involving 36 high school students from Sukabumi Regency as the research sample. The selection of the participants was made to create a supportive environment for the implementation and assessment of the didactic design that had been developed. To accumulate data regarding students’ scientific literacy, the assessment instruments that were designed following the PISA science framework were used. Students were tested in their capacity to give explanations for scientific phenomena, to assess and create scientific investigations, and to decipher scientific data. The teachers using these instruments then analyzed the scientific literacy data to ascertain the impact of the PBL-based didactic design. The research results indicate that the students ability to explain scientific phenomena was very strong but the ability to evaluate investigations and interpret data was rather moderate and therefore needed further support. These findings signify that the didactic PBL design facilitates students’ science literacy in learning the connection of scientific concepts with real-world problems, however, the refinement of the learning activities is necessary in order to maximize the development of higher-order evaluative and analytical skills.